PERAN AMAL USAHA MUHAMMADIYAH DALAM PENGEMBANGAN EKONOMI UMAT DI KOTA TANGERANG - Yusrizal (Yasi Learning Education Research, 2025)
Muhammadiyah Charity in various regions, including Tangerang City, is a manifestation of the organization's efforts in spreading da'wah and realizing a progressive Islamic society. The research aims to analyze the role of Muhammadiyah Business Charity (AUM) in the economic development of the ummah in Tangerang City through a qualitative approach with a case study method. Data collection was carried out through in-depth interviews, field observations, and document analysis to comprehensively understand the contribution of AUM. The focus of the research includes AUM managers and fostered MSME actors who interact directly with Muhammadiyah's economic empowerment program. Primary data was obtained from AUM managers and business actors, while secondary data came from literature studies and institutional reports. The analysis shows that AUM performance is in the good category, characterized by institutional effectiveness, program relevance, and accountable governance. AUM plays a significant role as an economic driver of the ummah through educational, health, social, and business unit services based on sharia economic principles that encourage social justice and economic inclusivity. However, some aspects such as the quality of human resources and business model innovation are still in the poor category so they need strengthening. The impact of AUM is evident in community empowerment, increased access to services, and its contribution to equitable welfare. This finding confirms that optimizing the role of AUM requires synergy between strong internal capacity and adaptability to external dynamics for the economic sustainability of the people in Tangerang City.